On Becoming a Scholar What Every New Academic Needs to Know - Jansen, Jonathan; Visser, Daniel (African Minds, 2022)
The origins of On Becoming a Scholarlie in the realisation that there is a need for a vademecum, a handy compendium of ideas, plans and strategies for building a productive and fulfilling academic career to guide the host of prospective academics. On Becoming a Scholaris geared to help relatively new scholars to construct personal futures and to find their way through the 21st century university. It is intended to be a map, and like any map it does not contain all the contours and details of the landscape, but rather seeks to reveal the important pathways and milestones in the journey to becoming an established academic. Drawing on highly experienced academics and accomplished professors in their different fields, as well as promising younger academics already on their way, this book cover a concentratedresource of practical wisdom. The topics are broad and, cumulatively, they seek to answer the many questions that experiencedmentors encounter every day in their work with new academics.